Pengembangan Handout Berbasis Guided Note Taking untuk Meningkatkan Minat Belajar pada Materi Elektrolit dan Nonelektrolit - Fatria Dewi; Lutfi Praidha Amyarsita; Syamsurizal Syamsurizal (Hydrogen: Jurnal Kependidikan Kimia, 2022)
The research carried out has the aim ofknowing the level of student interest in learning by using handout teaching materials based on guided note taking in class X MIPA 1 SMAN 6 Jambi City in the 2021/2022 academic year. Interest in learning is still a problem for learning in schools because the lack of interest in student learning can cause learning to be less conducive and effective during the learning process. This research was conducted 2 tests, namely individual test and small group test. The measurement of interest in learning has 5 indicators that are measured objectively, namely initiative, earnest, enthusiastic, reflective and responsive thinking. The research data were obtained from interviews, expert validation sheets, teacher assessments, student responses and student interest assessments. The results of student responses to the individual test obtained a percentage of 73% which is included in the good category.